(untitled) (Research, Society and Development, 2022)
Introduction: the integration of speech therapy and physical therapy interventions is positive in improving the vocal performance of voice professionals. Objective: to analyze the effects after practice performed through vocal exercises (Semi-occluded Vocal Tract Exercises-SOVTE) and respiratory exercises (use of the Respiron Classic® device). Method: intervention study (pre and post), called Vocal and Respiratory Conditioning (CVR), which included three voice professionals who filled in before and after instruments to assess the self-reported presence of voice handicap (VDI-10), vocal fatigue ( IFV) and symptoms after their presentations (EASE-BR); were evaluated in terms of vocal quality parameters and maximum phonation time; and assessment of respiratory muscle strength and maximum voluntary ventilation. The exercises presented during the meetings were also performed at home, with a record of vocal and respiratory comfort (score from 0 to 10). Data were analyzed descriptively and subjected to statistical tests. Results: the indices referring to the instruments applied showed, in the post-mortem period, less disadvantage and vocal fatigue. The scores given to vocal and respiratory comfort were progressively better during the program (p<0.001). In the voice assessment, an increase in the maximum phonatory time and maintenance of some parameters of vocal quality was observed. Endurance test indices (MVV) and MIP and MEP increased after training. In the participants’ reports, there was also a record of improvement in terms of physical conditions. Conclusion: the CVR program registered an overall improvement in vocal and respiratory conditioning, with a positive impact on the vocal performance of the participants.